Biotechnology, agriculture and development - Phillips, Peter W. B. (Edward Elgar Pub. Ltd, 2015)
Recommended readings (Machine generated): Philipp Aerni (2011), 'Do Political Attitudes Affect Consumer Choice? Evidence from a Large-Scale Field Study with Genetically Modified Bread in Switzerland' -- Akhter Ali and Awudu Abdulai (2010), 'The Adoption of Genetically Modified Cotton and Poverty Reduction in Pakistan' -- Julian M. Alston, Michele C. Marra, Philip G. Pardey and T.J. Wyatt (2000), 'Research Returns Redux: A Meta-Analysis of the Returns to Agricultural R&D' -- Klaus Ammann (2007), 'Reconciling Traditional Knowledge with Modern Agriculture: A Guide for Building Bridges' -- Kym Anderson (2010), 'Economic Impacts of Policies Affecting Crop Biotechnology and Trade' -- Arnab K. Basu and Matin Qaim (2007), 'On The Adoption of Genetically Modified Seeds in Developing Countries and the Optimal Types of Government Intervention' -- Volker Beckmann, Claudio Soregaroli and Justus Wesseler (2006), 'Coexistence Rules and Regulations in the European Union' --
The recommended readings are available in the print version, or may be available via the link to your library's holdings
Keywords: Agricultural biotechnology; Food -- Biotechnology; Genetically modified foods; Agricultural innovations; Food industry and trade -- Technological innovations; Agriculture -- Economic aspects; Economic development; Electronic books